The government's Role with Respect to Honorary Workers is Delineated in the 2014 State Civil Apparatus Act. - Supian; Herlina Hanum Harahap (Inovasi Pratama Internasional. Ltd, 2024)
The objective of this study is to determine the role of the government with regards to honorary workers in compliance with Law No. 5 of 2014 concerning the State Civil Apparatus. Furthermore, it seeks to identify the efforts and policies of the Serdang Bedagai Regency government in organizing personnel administration of honorary workers. Furthermore, this study will examine whether there has been an impact on the Government of Serdang Bedagai Regency in accordance with Law Number 5 of 2014, as well as the impact of Law Number 5 of 2014 on honorary workers in the region. The empirical juridical method was employed in this study. Data were collected through interviews and documentation. Upon completion of the data processing stage, it is evident that the Serdang Bedagai Regency Government has consistently implemented its policy of administering honorary staff and similar personnel through the establishment of formal legality, as evidenced by the issuance of a decree (SK) of honorary staff, which was originally initiated by the Regent or Regional Official. This practice has continued, with no changes being made, for the 2019 and subsequent years. Furthermore, the decree has been transferred to each OPD, where it will be administered by both the head of the agency and the head of the service within the agency. In addition, it should be noted that, in order for the Serdang Bedagai Regency Government to function effectively and efficiently, it still requires honorary staff, such as operators, security personnel, and cleaning personnel, whose roles are essential to the smooth running of operations.